Work visas and return migration: how migration policy shapes global talent. Issue 7 (19th May 2022) - Jacobs, Elizabeth
ABSTRACT: The recruitment and retention of foreign talent are crucial dimensions of the global education and labour markets. This paper examines how entwined migration policies and corporate practices shape the development and flow of international skill. I pair an original dataset of employment histories with 105 interviews with skilled migrants and institutional actors to examine the process of skill and knowledge formation among foreign-born workers in the United States and return migrants in India. The findings show that employer-sponsored visas constrain the development of foreign skill and inefficiencies in the implementation of H-1B visas andgreen cards are contributing to return migration. Return migrants leave the United States with knowledge and skills in STEM and business that they developed while studying and working in the United States. At the same time, multinational employers are increasingly conceptualising migration experience as a skill, giving return migrants an advantage in their home labour markets. The findings of this paper illustrate how interactions between state and corporate institutions shape the process of skill formation throughout the migration journey.